Emission Characteristics of Hazardous Air Pollutants from Construction Equipment - Sungwoon Jung; Sunmoon Kim; Yunsung Lim; Jongtae Lee; Taekho Chung; Heekyoung Hong; Sunhee Mun; Seunghwan Lee; Woojun Jang; Jaehyun Lim (Aerosol and Air Quality Research)
Abstract The emission characteristics of mobile air pollution sources belonging to the non-road sector have yet to be thoroughly investigated, especially when compared to those of on-road vehicles. Hence, the present study employed an engine dynamometer to evaluate the emissions of a diesel engine complying with Tier 3 standards during various driving modes (KC1-8, NRSC, and NRTC) and a portable emissions measurement system (PEMS) to assess those of two excavators, one complying with Tier 3 and the other with Tier 4 standards, during real-world working and driving conditions. The characteristics and chemical composition of the emitted regulated pollutants (carbon monoxide (CO), non-methane hydrocarbon (NMHC), nitrogen oxide (NOx), and particulate matter (PM)) and hazardous air pollutants (HAPs), e.g., volatile organic compounds (VOCs), aldehydes, and polycyclic aromatic hydrocarbons (PAHs), were then determined. For the regulated pollutants, NRTC mode generated the highest emissions owing to the rapid changes in engine load and speed during transitions. As a result of the after-treatment systems, which utilized a diesel oxidation catalyst (DOC) and selective catalytic reduction (SCR), CO, NMHC, and NOx emissions from the Tier 4-compliant excavator were lower than those from the Tier 3-compliant diesel engine and excavator. The operating conditions of the diesel engine and construction equipment as well as the after-treatment systems significantly affected the composition of the non-methane volatile organic compound (NMVOC) emissions, which were dominated by alkanes that comprised 23 detected species. Sampling the particle-phase PAHs, we found phenanthrene, fluoranthene, and naphthalene; furthermore, we estimated the concentrations of the gas-phase PAHs with models to obtain the total PAH concentrations. Formaldehyde, which contributed the largest fraction of the aldehydes, was more abundant than the other species. Thus, emissions from non-road sources, including construction equipment, must be controlled because of the considerable health risks from pollutants such as formaldehyde and benzene. Our results will aid in the establishment of a national emission inventory for HAPs.